Pemberdayaan Ekonomi Keluarga Prasejahtera Melalui Pemanfataan Sumber Daya Keluarga dan Lahan Pekarangan - Bartin, Tasril; Irmawita, Irmawita; Wisroni, Wisroni (Universitas Negeri Padang, 2018)
Community and family empowerment activities are classic activities that are currently still underestimated by many parties, but this is still relevant and urgent when linked to community service programs. This community service program is proven to have a direct impact on efforts to improve the quality of life of the community, especially for disadvantaged families or disadvantaged families. Through this paper, the authors raise several positive aspects that can be obtained from several stages of the implementation of community service conducted by Padang State University in Nagari Lubuk Jantan Tanah Datar Regency. The focus of the activity is the empowerment of pre-prosperous family economies through the utilization of family resources and yards. The election of Nagari Lubuk Jantan is based on the consideration that this area is relatively many target groups or communities that are still underdeveloped in various aspects of life, especially in the education aspects, social aspects, and cultural aspects, and low levels of welfare, while they have relatively large family members as well as large yards that are not used optimally. The results of these community service activities have a significant impact, including: increased public knowledge about family problems and potential, the community gets an understanding in increasing family income through the management of family resources, and skills in improving the family economy by choosing and cultivating plants of economic value in the yard around residential areas, especially for economically weak communities. It is expected that all parties, including universities, regional governments, the private world, and community leaders, can increase their awareness of the family empowerment program, especially in optimizing the utilization of the potential of family resources such as human resources, family assets and time. Therefore, in the future, a variety of scientific studies and a more comprehensive service program breakthrough and totality related to efforts to improve the quality of the family will lead to a more dignified prosperous family.Keywords: Family Resources, Disadvantaged Families, Yard